Comparison of Accuracy of WHARFE Assessment and Pederson Difficulty Index for Predicting Surgical Difficulty in Patients with Impacted Mandibular Third Molar Surgery: WHARFE and Pederson Index in Predicting Surgical Difficulty - Ram, Gobind; Ali, Anwar; Khatoon, Safia; Iqbal, Syeda Noureen; Sultan, Daud; Zulfiqar, Roma (Pakistan Journal of Health Sciences, 2024)
The extraction of a mandibular impacted third molar was a highly prevalent oral surgical procedure. Assessing the surgical difficulty of impacted mandibular third molar extraction was crucial for planning and executing successful procedures. Various assessment tools, such as the WHARFE Assessment and Pederson's Difficulty Index, have been developed to aid clinicians in predicting the complexity of these surgeries. Objective: To determine the accuracy of the WHARFE assessment and Pederson’s difficulty index for predicting surgical difficulty in patients with impacted mandibular third molar surgery. Methods: A descriptive cross-sectional study was conducted at the department of Oral and maxillofacial surgery, Dow university of health sciences, Karachi, Pakistan. Data were collected in time duration of six months by employing non-probability convenience sampling technique. SPSS version 26.0 was used for data analysis. Chi-square test was applied with a significant level of p value <0.05. Results: The WHARFE assessment demonstrated an accuracy of 60.0% in predicting surgical difficulty, with a corresponding p-value of (p=0.001). Similarly, Pederson's difficulty index assessment showed an accuracy of 54.5% in predicting surgical difficulty, with a p-value of (p=0.232). Conclusion: Both assessments showed some ability to predict surgical difficulty, WHARFE assessment demonstrated a strong predictive accuracy, and the differences observed did reach statistical significance (p-value 0.001).